2003
DOI: 10.1002/em.10201
|View full text |Cite
|
Sign up to set email alerts
|

Deletion, rearrangement, and gene conversion; genetic consequences of chromosomal double‐strand breaks in human cells

Abstract: Chromosomal double-strand breaks (DSBs) in mammalian cells are usually repaired through either of two pathways: end-joining (EJ) or homologous recombination (HR). To clarify the relative contribution of each pathway and the ensuing genetic changes, we developed a system to trace the fate of DSBs that occur in an endogenous single-copy human gene. Lymphoblastoid cell lines TSCE5 and TSCER2 are heterozygous (+/-) or compound heterozygous (-/-), respectively, for the thymidine kinase gene (TK), and we introduced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
64
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 63 publications
(69 citation statements)
references
References 52 publications
3
64
2
Order By: Relevance
“…The present data lend molecular support to these observations by directly measuring both efficiency and accuracy of NHEJ itself, in a chromosome context. These data are also in line with the notion that in human lymphoblastoid cells, NHEJ repair of I-SceI-induced DSB mainly results in small or no deletions (Honma et al, 2003(Honma et al, , 2007. In addition our data also revealed that the accuracy of end joining is affected by the dynamic progression through S phase.…”
Section: Discussionsupporting
confidence: 91%
“…The present data lend molecular support to these observations by directly measuring both efficiency and accuracy of NHEJ itself, in a chromosome context. These data are also in line with the notion that in human lymphoblastoid cells, NHEJ repair of I-SceI-induced DSB mainly results in small or no deletions (Honma et al, 2003(Honma et al, , 2007. In addition our data also revealed that the accuracy of end joining is affected by the dynamic progression through S phase.…”
Section: Discussionsupporting
confidence: 91%
“…Nonconservative repair processes abrogated the activity of the reporter genes and enabled cells to survive in selection media. In another experimental system [19], a DSB was introduced in an intron of the endogenous Tk gene of a human lymphoblastoid cell line, and aberrant DNA repair events were recovered by selecting for cells that had lost Tk activity. However, this assay favors the recovery of large scale changes, such as long deletions, and does not provide a means of assessing the frequency of short deletions.…”
Section: Introductionmentioning
confidence: 99%
“…Since genetic changes at chromosome level are considered to be caused by chromosome break or DNA double-strand break (DSB), the repair of DSB was evaluated by our model system (Fig. 6) (Honma et al, 2003). The repair of DSBs is considered to be mainly due to two pathways, non homologous end-joining (NHEJ) and homologous recombination (HR).…”
Section: Dsb-repair Evaluation For Detection Of Adaptive Responsementioning
confidence: 99%
“…The repair of DSBs is considered to be mainly due to two pathways, non homologous end-joining (NHEJ) and homologous recombination (HR). The details of methodologies for evaluating the above DSB repair were already described in our previous paper (Honma et al, 2003, Honma etal., 2007, and Yatagai et al sequence containing the recognition sequence for the restriction enzyme I-SceI was introduced at the region upstream of exon 5 in the TK + allele of TK6 cells. The cells containing this insert were designated TSCE5.…”
Section: Dsb-repair Evaluation For Detection Of Adaptive Responsementioning
confidence: 99%